Principles- Versus Rules-Based Output Statistical Disclosure Control In Remote Access Environments - Felix Ritchie; Mark Elliot (IASSIST Quarterly, 2015)
Principles- Versus Rules-Based Output Statistical Disclosure Control In Remote Access Environments